Affection in Interpretation According to Abi Hayyan Al-Andalusi (d. 745 A.H) Through his Interpretation of Al-Bahr Al-Moheet Surat Al-Baqarah as a Model - Khalaf , Murad; Saleh , Nafeh (Islamic Sciences Journal, 2023)
ABSTRACT Attributing to interpretation is a synthetic term meaning an attempt to convey the verse to a meaning that the word may carry with the presence of the apparent meaning without a legitimate need And cost in interpretation is a term similar to what is in interpretation and indicative interpretation, as the difference between them is the fulfillment of the conditions of each of them, and then we went back to this research . On knowing the obligatory in the interpretation and we spoke successively about Abu Hayyan Al-Andalus and how he explained and identified the pretentious sayings that he mentioned in his interpretation of Al-Bahr Al-Moheet and then refuting them and clarifying the sayings of the commentators who were charged with the interpretation of some verses.